Facet Engineering of Advanced Electrocatalysts Toward Hydrogen/Oxygen Evolution Reactions - Wang, Changshui; Zhang, Qian; Yan, Bing; You, Bo; Zheng, Jiaojiao; Feng, Li; Zhang, Chunmei; Jiang, Shaohua; Chen, Wei; He, Shuijian (Nano-Micro Letters, 2023)
The electrocatalytic water splitting technology can generate high-purity hydrogen without emitting carbon dioxide, which is in favor of relieving environmental pollution and energy crisis and achieving carbon neutrality. Electrocatalysts can effectively reduce the reaction energy barrier and increase the reaction efficiency. Facet engineering is considered as a promising strategy in controlling the ratio of desired crystal planes on the surface. Owing to the anisotropy, crystal planes with different orientations usually feature facet-dependent physical and chemical properties, leading to differences in the adsorption energies of oxygen or hydrogen intermediates, and thus exhibit varied electrocatalytic activity toward hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). In this review, a brief introduction of the basic concepts, fundamental understanding of the reaction mechanisms as well as key evaluating parameters for both HER and OER are provided. The formation mechanisms of the crystal facets are comprehensively overviewed aiming to give scientific theory guides to realize dominant crystal planes. Subsequently, three strategies of selective capping agent, selective etching agent, and coordination modulation to tune crystal planes are comprehensively summarized. Then, we present an overview of significant contributions of facet-engineered catalysts toward HER, OER, and overall water splitting. In particular, we highlight that density functional theory calculations play an indispensable role in unveiling the structure–activity correlation between the crystal plane and catalytic activity. Finally, the remaining challenges in facet-engineered catalysts for HER and OER are provided and future prospects for designing advanced facet-engineered electrocatalysts are discussed. Highlights: 1 The crystal facets featured with facet-dependent physical and chemical properties can exhibit varied electrocatalytic activity toward hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) attributed to their anisotropy. 2 The highly active exposed crystal facets enable increased mass activity of active sites, lower reaction energy barriers, and enhanced catalytic reaction rates for HER and OER. 3 The formation mechanism and control strategy of the crystal facet, significant contributions as well as challenges and perspectives of facet-engineered catalysts for HER and OER are provided.